Changes in the contour of karyology and histoarchitecture of the primary respiratory organ in the fish Oreochromis mossambicus (Peters, 1852) inhabiting the polluted estuarine ecosystem. (15th February 2022) - Punitha, Subramaniam; Krishnamurthy, Rajamanickkam; Elumalai, Kuppusamy; Mahboob, Shahid; Al-Ghanim, Khalid A.; Ahmed, Zubair; Mustafa, Ahmed; Govindarajan, Marimuthu
Abstract: The wetland ecosystem (WE) is subject to pollution by many anthropogenic activities, including domestic and industrial effluents. These effluents may contain toxic heavy metals that can interact within the aquatic ecosystem and have a capacity to disturb the metabolic activities, histological profile, and genetic structure and functions in aquatic species inhabiting the environment. The present study observed the karyological and histological alterations in gills of the freshwater fish, Mozambique tilapia, Oreochromis mossambicus in two different sublethal concentrations (1% and 3%) of heavy metals in 7, 15, and 30 days of experimental periods. The heavy metals induced various structural damages such as ring chromosome, sister chromatid exchange, acrocentric association region, condensed chromosomal morphology, heterochromatin region, and nucleolar organizer region in the chromosomes of O. mossambicus treated with 1% and 3% sublethal concentrations of water sample collected from Pallikaranai wetland ecosystem. Gills exposed to 1% and 3% effluent exhibited several variations in the respiratory surfaces of gill arches or lamellae in the light and scanning microscopical study. The gills exposed to 1% concentration for 30 days showed marked necrosis, and the secondary lamellae showed the lamellar membrane's dissolution. Exposure of gills to raw effluent in the field condition was observed in the presence of Cd, Pb, Cr, Cu, and Zn. Thus, this present study shows the environmental deterioration by heavy metal pollution on the structure of the gills in tilapia.